Analisis Kebutuhan Multimedia Interaktif METUGI pada Siswa Kelas IV di SDN Burengan 3 Kediri - Setyo Adelia Putri; Kharisma Eka Putri; Sulistiono Sulistiono (Lembaga Yasin AlSys, 2026)
Science learning on the topic of energy transformation in elementary schools still faces various challenges, particularly in helping students understand abstract concepts. The limited use of learning media that remain centered on textbooks and lecture methods causes students to be less active and to become easily bored during the learning process. This study aims to analyze the need for developing METUGI interactive multimedia on the topic of energy transformation for Grade IV students at SDN Burengan 3 Kediri. This study used a descriptive qualitative approach with data collection techniques in the form of interviews and questionnaires. The research subjects consisted of 28 Grade IV students. The questionnaire instrument used a Guttman scale with Yes and No response options. The results show that 21 students had difficulty understanding energy material, 20 students more easily understood the material through visual media, animation, and sound, and 25 students were interested in learning using games or interactive quizzes. This finding indicates a strong need for the development of METUGI interactive multimedia as a science learning medium that is more concrete, engaging, and interactive. This study concludes that the development of METUGI interactive multimedia is needed to support students’ understanding of the concept of energy transformation in accordance with the learning characteristics of elementary school students. The implications of this study may serve as a basis for developing science learning media based on interactive multimedia that are relevant to students’ needs and the learning context in elementary schools. Keywords: Needs Analysis; Interactive Multimedia; Science Learning; Energy Transformation; Elementary School